Pendidikan Ekonomi Dalam Al-Qur’an: Analisis Surah Al-Baqarah Ayat 275-279 Dan Surah Al-Hasyr Ayat 7 - Muhaimin; Mahyuddin Barni (Yayasan Al-Afif, 2026)
This study examines economic education in the Qur’an with a focus on the prohibition of usury (riba) and the principle of wealth distribution in Surah Al-Baqarah verses 275–279 and Surah Al-Hasyr verse 7. The research problem addresses how the Qur’an constructs principles of economic education that are just and relevant to modern life. The purpose of this study is to analyze the values of Islamic economics contained in these verses and their implications for economic education in the Muslim community. This research employs a qualitative method using a thematic tafsir approach through library research, utilizing the Qur’an as the primary source along with classical tafsir works and Islamic economics literature. The findings indicate that the Qur’an firmly prohibits riba as a rejection of economic exploitation and emphasizes fair and inclusive wealth distribution. The study concludes that Islamic economic principles in the Qur’an have educational and practical impacts in fostering a just, ethical, and socially oriented economic system.